102k views
18 votes
Evaluate the expression

Evaluate the expression-example-1
User Madhukar
by
5.3k points

2 Answers

9 votes

Answer:

36

Explanation:

Given expression:


(10 - 3 + 5)^(2)} * (1)/(4)

Simplify the expression in the parenthesis


\implies (12)^(2) * (1)/(4)

Simplify the exponents in the expression:


\implies (12) * (12) * (1)/(4)


\implies 144 * (1)/(4)

∴ Recall that: (a × 1/b = a ÷ b)


\implies 144 / 4

Simplify the expression:


\implies 144 / 4


\implies \boxed{36}

User Ronginat
by
4.5k points
6 votes

Answer:

C) 36

Explanation:

Given expression:


\frac14(10-3+5)^2

Following the order of operations, carry out the operations inside the bracket first:


\implies \frac14(7+5)^2


\implies \frac14(12)^2

Now carry out the exponent:


\implies \frac14(144)

Finally:


\implies (144)/(4)=36

User Dashton
by
4.4k points